Compartmentalized spatial profiling of the tumor microenvironment in head and neck squamous cell carcinoma identifies immune checkpoint molecules and tumor necrosis factor receptor superfamily members as biomarkers of response to immunotherapy - Sadeghirad, Habib; Liu, Ning; Monkman, James; Ma, Ning; Cheikh, Bassem Ben; Jhaveri, Niyati; Tan, Chin Wee; Warkiani, Majid Ebrahimi; Adams, Mark N.; Nguyen, Quan; Ladwa, Rahul; Braubach, Oliver; et al. (Frontiers in Immunology, 2023)
Mucosal head and neck squamous cell carcinoma (HNSCC) are the seventh most common cancer, with approximately 50% of patients living beyond 5-years. Immune checkpoint inhibitors (ICIs) have shown promising results in patients with recurrent or metastatic (R/M) disease, however, only a subset of patients benefit from immunotherapy. Studies have implicated the tumour microenvironment (TME) of HNSCC as a major factor in therapy response, highlighting the need to better understand the TME, particularly by spatially resolved means to determine cellular and molecular components. Here, we employed targeted spatial profiling of proteins on a cohort of pre-treatment tissues from patients with R/M disease to identify novel biomarkers of response within the tumour and stromal margins. By grouping patient outcome categories into response or non-response, we show that immune checkpoint molecules, including PD-L1, B7-H3, and VISTA, were differentially expressed. Patient-responders possessed significantly higher tumour expression of PD-L1 and B7-H3, but lower expression of VISTA. Analysis of response subgroups by Response Evaluation Criteria in Solid Tumours (RECIST) criteria indicated that tumour necrosis factor receptor (TNFR) superfamily members including OX40L, CD27, 4-1BB, CD40, and CD95/Fas, were associated with immunotherapy outcome. OX40L expression in tumour regions was higher in patient-responders than those with progressive disease (PD), while other TNFR members, CD27 and CD95/Fas were lower expressed in patients with a partial response (PR) compared to those with PD. Furthermore, we found that high 4-1BB expression in the tumour compartment, but not in the stroma, was associated with better overall survival (OS) (HR= 0.28, p-adjusted= 0.040). Moreover, high CD40 expression in tumour regions (HR= 0.27, p-adjusted= 0.035), and high CD27 expression in the stroma (HR= 0.2, p-adjusted=0.032) were associated with better survival outcomes. Taken together, this study supports the role for immune checkpoint molecules, and implicates the TNFR superfamily as key players in immunotherapy response in our cohort of HNSCC. Validation of these findings in a prospective study is required to determine the robustness of these tissue signatures.